JOURNEY OF GREEN REVOLUTION IN INDIA WITH FOCUS ON PUNJAB - Singh, Harjinder (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Green Revolution marked a transformation in Indian agriculture particularly in Punjab. It is main state to the production of wheat (Triticum aestivum L.) and rice (Oryza sativa L.). This review examines the historical context and consequences of the Green Revolution, emphasizing the dramatic improvements in crop yields and national food security. Beginning in the 1960s, the introduction of high-yielding crop varieties, chemical fertilizers, irrigation systems shifted India from food scarcity to self-sufficiency. While the Green Revolution is widely credited with averting famine and reducing poverty, it also showed some negative effect. This paper analyses both the achievements and limitations of this agricultural transformation, offering a comprehensive perspective on one of the most significant agrarian movements in modern India.